Late Paleo-Indian Period Lithic Economies, Mobility, and Group Organization in Wisconsin - (:unkn) unknown (My University, 2016)
The following dissertation focuses upon the organization of Pleistocene / Holocene period lithic technology in Wisconsin circa 10,000 – 10,500 years before present. Lithic debitage and flaked stone tools from the Plainview/Agate Basin components of the Heyrman I site (47DR381), the Dalles site (47IA374), and the Kelly North Tract site at Carcajou Point (47JE02) comprise the data set. These Wisconsin sites are located within a post glacial Great Lakes dune environment, an inland drainage/riverine environment, and an inland wetland/lacustrine environment. An assemblage approach is used to examine the structure of each site’s lithic economy. This broad approach to lithic organization is taken in order to maximize the number of lithic categories for comparison and avoid the more narrow scope of understanding that can result from focusing upon a single lithic category. Prior research has shown that the examination of lithic technology provides a well-founded basis for inference regarding small group economy, mobility, and organization. Current investigations suggest that small groups present during the Pleistocene/Holocene transition may have practiced two bi-lateral economies, one based more upon lower group mobility or logistical mobility, the other based more upon residential or higher group mobility. These distinctions are important given that our understanding of the correlation between resource use, mobility, and small group organization with environment may be critical in adapting to current socioeconomic problems. Although few Pleistocene/Holocene transition period sites have been systematically investigated in Wisconsin, this examination suggests that both early Paleoindian and late Paleoindian/Early Archaic economies and mobility strategies varied with localized environments. Examination of the data recovered from the Heyrman I, Dalles, and North Tract sites increases the understanding of economic adaptations, small group mobility, and group structure across multiple environments and provides further insight into human responses to changing resource conditions.
Keywords: Agate Basin; Climate; Door County; Paleoindian; Pre-Agate Basin; Wisconsin